Isolation and Characterization of Acinetobacter baumannii from Chicken Meat Samples in North India - Kumar, Sunil; Anwer, Razique; Yadav, Mukesh; Sehrawat, Nirmala; Kumar, Vikas; Sharma, Anil Kumar (Asian Journal of Biological and Life Sciences)
Meat is consumed as food and rich source of nutrients in many parts of the world. Due to poor hand hygiene and other sources, meat samples get contaminated with many bacterial species. Most of the pathogenic bacteria are often traced in hospital settings but some of them in the recent years have been recovered from outside hospital environment like; Acinetobacter baumannii, Salmonella, E. coli, Clostridium, Staphyloccus, Klebsiella, and Pseudomonas species. The aim of the study was to investigation of bacterial load, types and their resistance profile in the chicken meat collected from various slaughterhouses of North India. A total of 50 samples (meat, surface swabs and knife swabs) were processed in the microbiology laboratory. CFUs were counted by Spread Plate Count (SPC) method and cultured bacteria were analyzed by MALDI-TOF MS. Antimicrobial susceptibility testing was performed using Kirby-Bauer disk diffusion assay as per CLSI guidelines. We isolated and characterized the potential pathogenic bacteria like; E. coli (5), Acinetobacter baumannii (4), Enterobacter cloacae (2), Pseudomonas aeruginosa (1) and Providencia stuartii (1) from raw meat, knifen and surface samples from the retail meat shop in Mullana territory. Although a number of pathogenic strains were isolated from meat samples, a low resistance was reported for all the isolates recovered from meat samples, comparative to that of clinical Isolates in the region.
Keywords: Acinetobacter baumannii; Chicken meat; E. coli; Food Poisoning; MALDI-TOF MS